Legal Analysis of the Crime of Skimming in Indonesia According to the Electronic Information and Transactions Law (ITE) Number 11 of 2008 concerning Information and Electronic Transactions - Ervina Sari Sipahutar; Indra Gunawan Purba; Anjani Sipahutar (Budapest International Research and Critics University, 2022)
Crime in cyberspace presents new and serious problems on an international scale and is very complex in efforts to empower the law to deal with them. Economic crimes including Automatic Teller Machine (ATM) cards and theft of money are the second problem that is very worrying for the banking world, especially those committed by Asia. The legal situation in Indonesia, in particular, the laws and regulations made in the last twenty-five years is very easy to swallow. Objectively, this happens because changes in society in the political, economic, social, and cultural fields are going so fast, so that the law is easily left behind. Subjectively, various laws and regulations are made to overcome instant situations, so they pay less attention to insight. In reality, cyber activities (virtual world or the internet), are no longer simple, but quite complicated, because their activities are no longer limited by the territory of a country, which can be easily accessed anytime and from anywhere. Losses can occur, both to the perpetrator of the transaction and to other people who have never made a transaction, for example, the theft of bank customer funds through skimmer mode (procurement of Automated Teller Machines or so-called ATM cards). Advances in information technology that became the beginning of the existence of cybercrime, can legally have an impact on the law, which regulates this matter. Crimes like this can be categorized as acts of theft / fraud contained in the Criminal Code (KUHP) and Law no. 11 of 2008 concerning Information and Electronic Transactions, hereinafter referred to as UU ITE. Anyone in the city or village who already has an Automatic Teller Machine (ATM), especially in a big city, must have at least one plastic card with magnetic tape, which is often called an Automatic Teller Machine (ATM) card.